Progressive cerebellar ataxia, proximal neurogenic weakness and ocular motor disturbances: hexosaminidase A deficiency with late clinical onset in four siblings - Hund, Ernst; Grau, Armin J.; Fogel, Wolfgang; Forsting, Michael; Cantz, Michael; Kustermann-Kuhn, B.; Harzer, K.; Navon, R.; Goebel, H. H.; Meinck, Hans-Michael (Journal of the neurological sciences, 1997)
Tay-Sachs disease is a genetically determined neurodegenerative disorder, resulting from mutations of the hexosaminidase (Hex) A gene coding for the α-subunit of β-d-N-acetyl-hexosaminidase. Clinically, there is severe encephalomyelopathy leading to death within the first few years of life. Hex A activity is usually absent in tissue and body fluids of these patients. Juvenile and adult Hex A deficiencies are less severe but rare variants with some residual Hex A activity. All these variants are most prevalent among Ashkenazi Jews. We describe a non-Jewish family in which four adult brothers and sisters had markedly reduced Hex A activities and onset of symptoms in the second decade of life. The phenotypical expression was remarkably homogeneous, consisting in a combination of slowly progressive motor neuron disease, ataxia and ocular motor disturbances. None of the patients were demented at this stage of their illness. Magnetic resonance studies showed severe cerebellar atrophy, but were otherwise normal. Hex A deficiency was established by biochemical measurements in the serum and skin fibroblasts using the fluorogenic substrates 4-MUG and 4-MUGS as well as by gel electrophoresis. Molecular genetic studies revealed that the patients are compound heterozygotes for the ‘adult’ mutation Gly269 → Ser and the ‘infantile’ 4-base insertion in exon 11 of the Hex A gene. © 1997 Elsevier Science B.V.
Gesehen am 11.07.2024